The American Religious Experience a Concise History. - Bridgers, Lynn. (Lanham : Rowman & Littlefield Publishers, 2006)
The American Religious Experience is an accessible and unique rendition of American religious history. Focusing on Christianity in America, it also integrates the inter-religious, inter-denominational and multi-cultural dimensions of American religious history. The book unfolds consistent tensions between dominant streams of American Christianity and groups relegated to the periphery - groups with roots in visionary traditions, emotionalized religious practice, or ethnic and racial perspectives.
16 The California Missions and the Hispanic Southwest17 Raids, Ghosts, and Renewal; 18 Mormon Country; 19 Gold Mountain; 20 Pluralism and Periphery; Resources for Further Reading; Index; About the Author.
Description based on print version record.
Keywords: African Americans -- Religion; United States -- Religion -- History; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books